Estimasi Volume dan Berat Buah Belimbing menggunakan Metode Cakram dan Regresi Linear berbasis Kamera pada Raspberry Pi - Muhammad Rifqi Radifan Masruri; Hurriyatul Fitriyah; Eko Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Evaluating starfruit by looking at its size can be done using a conventional method. This method requires a lot of human resources and time. To speed up the process, digital image processing technology is used. Starfruit is a fruit that is very popular in Indonesia. Sweet and sour taste in starfruit is very suitable to be made into salad. Starfruit becomes a challenge because it has five sections and does not resemble a solid. There is a modified method for adjusting starfruit characteristics. This study uses volume and weight parameters in evaluating. Digital images are taken using a camera connected to the Raspberry Pi. The image obtained is processed for segmentation. Information from the results of segmentation will be used in a modified cylindrical method to produce a volume. Volume will be used in the linear regression method to produce weight. The accuracy of the volume method obtained was 86.64% and the accuracy of the weight method was 86.43% with an average execution time of 3.45 seconds. This solution can be an example of the image processing technology development.